Bee & Flea and the fall fiasco - Humphrey, Anna (Humphrey, Anna. Bee & Flea, 2024)
"The third adventure of crime-solving pair Bee and Flea, this time exploring how the backyard critters adapt and prepare for winter. The weather is turning cold, and Bee notices that the animals in the big backyard are acting ... odd. Flea is uncharacteristically sleepy, the yard is strangely quiet, and then there's the commotion at the compost heap--a huge, round, orange object is looming over the earthworms! Bee and her new friend Fuzz, a woolly bear caterpillar, can't convince a very tired Flea to help, so Bee turns to her old bee colony for back up. She soon learns, however, that there's actually no emergency at all, and that the changes to the yard, including Flea's sleepiness, are perfectly normal adaptations for the coming winter. The insects and other critters are merely slowing down, settling in, and adapting to get through the sub-zero temperatures."--